(untitled) (Asian Journal of Medical and Biological Research, 2020)
Infection control practice is one of the major task performed by health care worker to reduce health care-associated infections (HACIs) in hospital. Health care-associated infections (HACIs) are common causes of illness and mortality among hospitalized patients including healthcare workers. The study aimed to identify the infection control practices in a district hospital. A cross sectional study was conducted from January to December, 2019 in a district hospital, Jashore, Bangladesh. Two hundred and twelve (212) Healthcare workers were selected purposively from this hospital and interviewed with a pre-tested semi-structured questionnaire. An observational check list was also used to observe the practices of that hospital. Among the healthcare workers 21 (9.9%) were doctor, 143 (67.5%) were nurse, 8 (3.8%) were technologist, 7 (3.3%) were aya, 13 (6.1%), were ward boy and 20 (9.4%) were cleaner. Collected data were checked, coded and transferred in to SPSS version 25 for analysis. Frequency, Percentage, Mean, SD, chi-square and other statistics were calculated. P-value less than 0.05 were set as statistically significant. The practices scores were categorized into good (≥80%), fair (59-79%), and poor (≤59%). The study found that overall of the respondents had fair practices regarding infection control. Among the doctors, nurse 7.3% had good practice, 51.8% had fair practice and 40.9% had poor practice. Among the supporting staffs 54.20% had Fair practice and 45.80% had Poor practice regarding infection control practices. Association between use of PPE with gender (p-.000) and with designation (p-.000) was evaluated and found highly significant relationship. Study findings suggest that in the existing infection control practices are often neglected and failed to protect healthcare workers and patients from hospital acquired infection. Asian J. Med. Biol. Res. June 2020, 6(2): 321-327